2022
DOI: 10.1021/acs.est.1c08914
|View full text |Cite
|
Sign up to set email alerts
|

BDE-99 Disrupts the Photoreceptor Patterning of Zebrafish Larvae via Transcription Factor six7

Abstract: Proper visual function is essential for collecting environmental information and supporting the decision-making in the central nervous system and is therefore tightly associated with wildlife survival and human health. Polybrominated diphenyl ethers (PBDEs) were reported to impair zebrafish vision development, and thyroid hormone (TH) signaling was suspected as the main contributor. In this study, a pentabrominated PBDE, BDE-99, was chosen to further explore the action mechanism of PBDEs on the disruption of z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
1
19
0
Order By: Relevance
“…Our study indicated that BTBPE causes developmental neurotoxicity in that it suppresses spontaneous movement, swimming activity, and visual acuity. This is consistent with another study indicating that PBDEs exposure can reduce movement and impairs visual acuity . Because TH plays a vital role in brain development, any disruptions in TH balance may impair neurological development .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our study indicated that BTBPE causes developmental neurotoxicity in that it suppresses spontaneous movement, swimming activity, and visual acuity. This is consistent with another study indicating that PBDEs exposure can reduce movement and impairs visual acuity . Because TH plays a vital role in brain development, any disruptions in TH balance may impair neurological development .…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies have shown that exposure to PBDEs impairs locomotion in embryonic and larval zebrafish . Other studies have suggested that thyroid hormone signaling participates in early eye development and regulation of photoreceptor patterns. ,, Hence, thyroid signaling disturbances caused by BTBPE may disrupt retinal development and neural function.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…81,82 The previous studies of our laboratory confirmed that PBDEs could damage rods and cones of the retina in zebrafish larvae as well as visually guided behaviors. 53,83 However, NIF vision, in contrast to traditional photoreceptors (rods and cones) and their image-forming functions, can rarely draw attention because it remains largely unexplored. In the current study, we made progress in demonstrating the importance of melanopsin and discovering that it acted not only as a new toxic target of BDE-47 in the retina of zebrafish but also as the initial event that disrupted the NIF pathway.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The zebrafish has emerged as a promising model for studying human eye disorders due to its remarkable similarities in anatomy, function, tissue composition, circuitry, and biochemistry with other vertebrates [ 31 ]. The highly conserved nature of zebrafish eyes among vertebrates has facilitated the successful modeling of numerous eye disorders [ 32 ], including cataracts, glaucoma, diabetic retinopathy, and age-related macular degeneration [ 16 , 33 ]. Zebrafish retinas exhibit the typical morphology found in vertebrate retinas, resembling adult retinas, and share both anatomical and functional similarities with human retinas [ 29 , 34 ].…”
Section: The Eye Structure Of Zebrafishmentioning
confidence: 99%